Improving Speaking Ability of the Second Year Students of SMK Negeri 1 Sinjai Through Small Group Discussion - Bahrun, St Rahmaniah (Universitas Islam Ahmad Dahlan (UIAD), 2020)
The objective of this research is to find out the improvement of studentsspeaking ability through small group discussion. The researcher applied quasiexperimental method. The population of this research is the second year students ofSMK Negeri 1 Sinjai. The researcher used total sampling technique, where two classeswere taken as sample, class of 2 AK 1 consisting of 20 students as the experimentalgroup, and class of 2 AK 2 with 20 students as a control class. The findings of the studyshowed that small group discussion activated the students. The result of data analysisshows that t-test value is greater than t-table value (4.81 > 2.042) at level of significance(p) = .05 with degree of freedom (df) = 19. It means that there is a significant differenceof speaking skill between two groups and it indicates that null hypothesis (H0) isrejected and alternative hypothesis (H1) is accepted. It is also supported by theobservation checklist analysis that shows the students’ progress from each treatment.Therefore, it can be concluded that the use of small group discussion can improve thestudents’ speaking skill.